2017
DOI: 10.7812/tpp/17-004
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-Induced Pancytopenia: A Case Report

Abstract: Introduction: Programmed death receptor-1 blockade with pembrolizumab is approved by the US Food and Drug Administration to treat patients with metastatic melanoma. Activating T cells to fight cancer may cause immune-mediated adverse events. Pembrolizumab-induced pancytopenia has not been previously reported in the medical literature, to our knowledge.Case Presentation: A 52-year-old Caucasian woman with a diagnosis of metastatic melanoma of the rectum experienced multiple adverse events along her course of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Anemia, neutropenia, thrombocytopenia, leukopenia and lymphopenia are reported to occur in 1%-10%, with febrile neutropenia and eosinophilia occurring in <1%. 2,3 However, few reports have described pancytopenia as an irAE. The mechanisms by which pembrolizumab induces pancytopenia are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia, neutropenia, thrombocytopenia, leukopenia and lymphopenia are reported to occur in 1%-10%, with febrile neutropenia and eosinophilia occurring in <1%. 2,3 However, few reports have described pancytopenia as an irAE. The mechanisms by which pembrolizumab induces pancytopenia are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Significant inflammatory or immune-mediated reactions included infusion-related reactions (3.0%), hypothyroidism (6.9%) and pneumonitis (3.6%) 4. Furthermore, newer reports described notable toxicities, such as type 1 diabetes mellitus,5 pancytopenia,6 colitis,7 keratoacanthomas,8 scleroderma,9 myasthenia gravis10 and uveitis 11. In terms of cardiotoxicity, two case reports are available in the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Ipilimumab and nivolumab are two checkpoint inhibitors that bind to CTLA‐4 and PD‐L1, respectively, and thereby reactivate cytotoxic T cells to destroy cancer cells. Both agents have been associated with immune‐related cytopenias, including red cell aplasia, autoimmune neutropenia, and thrombocytopenia . One case series of 11 patients showed that the incidence of immune thrombocytopenia purpura (ITP) with checkpoint inhibitors in melanoma patients was less than 1% and that the majority of cases had spontaneous resolution of thrombocytopenia .…”
Section: Discussionmentioning
confidence: 99%